Efficacy of lid everting suture in the management of involutional lower eyelid entropion using 4-0 silk versus 4-0 chromic catgut - Singh, SK; Das, H; Lavaju, P (Nepalese Journal of Ophthalmology, 2010)
Background: Involutional lower eyelid entropion is a common ophthalmic condition requiring surgical correction. Objective: To compare the efficacy of lid everting sutures in the management of involutional lower lid entropion using 4-0 silk versus 4-0 chromic catgut. Materials and methods: Fifty eyes with involutional lower eyelid entropion were enrolled into the study and divided randomly into two groups, A and B. Group A underwent lid everting suture with 4-0 chromic catgut and group B with 4-0 silk. The parameters assessed were pre- and post-operative lower lid excursion (LLE) and horizontal lid laxity (HLL). Statistical analysis: Data were plotted in the excel spread sheet and analyzed using SPSS 11.0 software program. The difference between the two groups was compared using Chi square test and unpaired t test. Results: While comparing the pre-operative and post-operative changes of HLL within the two groups separately, there was 63% reduction of HLL in group A (p=0.001) and 68% reduction (p=0.001) in group B. In group A, there was 48.2% improvement in LLE and in group B 52% postoperatively (p=0.001). The success rate in each group was 92%. The cost of surgery in group A was higher than that in group B (p=0.003). Conclusion: Lid everting suture by 4-0 silk is as effective as 4-0 chromic catgut. The cost of lid everting suture by 4-0 catgut is higher than that of 4-0 silk. The silk suture can be recommended for correction of lower lid involutional entropion in a country with low socioeconomic status. Key words: involutional entropion; lid laxity; lid excursion; lid everting suture DOI: 10.3126/nepjoph.v1i1.3672 Nep J Oph 2009;1(1):37-42